DUKUNGAN OPT-OUT DAN PERSEPSI NILAI E-BANKING - Ni Made Purnami (University of Merdeka Malang, 2015)
The aim of this study was to determine the effect of perceived firm commitment to privacy and trust in technology on perceived value from the firm with opt-out support as moderating variable. The study was conducted in Denpasar City with sample size of 120 e-banking user. Sample was determined by purposive sampling and data were collected by using questionnaires distributed directly. The data were processed with Moderate Regression Analysis (MRA). The results of this study indicate that perceived firm commitment to privacy and trust in technology is positively affect perceived value from the firm. Opt-out support are significantly moderate the relationship trust in technology and perceived value from the firm, and the results show a negatif coefficient, which means that the income level weaqken the influence of trust in technology on perceived value from the firm.